Biodiversity of ecosystems in an arid setting: The late Albian plant communities and associated biota from eastern Iberia - Barrón, Eduardo; Peyrot, Daniel; Bueno-Cebollada, Carlos A; Kvaček, Jiří; Álvarez-Parra, Sergio; Altolaguirre, Yul; Meléndez, Nieves (PloS one, 2023)
Deserts are stressful environments where the living beings must acquire different strategies to survive due to the water stress conditions. From the late Albian to the early Cenomanian, the northern and eastern parts of Iberia were the location of the desert system represented by deposits assigned to the Utrillas Group, which bear abundant amber with numerous bioinclusions, including diverse arthropods and vertebrate remains. In the Maestrazgo Basin (E Spain), the late Albian to early Cenomanian sedimentary succession represents the most distal part of the desert system (fore-erg) that was characterised by an alternation of aeolian and shallow marine sedimentary environments in the proximity of the Western Tethys palaeo-coast, with rare to frequent dinoflagellate cysts. The terrestrial ecosystems from this area were biodiverse, and comprised plant communities whose fossils are associated with sedimentological indicators of aridity. The palynoflora dominated by wind-transported conifer pollen is interpreted to reflect various types of xerophytic woodlands from the hinterlands and the coastal settings. Therefore, fern and angiosperm communities abundantly grew in wet interdunes and coastal wetlands (temporary to semi-permanent freshwater/salt marshes and water bodies). In addition, the occurrence of low-diversity megafloral assemblages reflects the existence of coastal salt-influenced settings. The palaeobotanical study carried out in this paper which is an integrative work on palynology and palaeobotany, does not only allow the reconstruction of the vegetation that developed in the mid-Cretaceous fore-erg from the eastern Iberia, in addition, provides new biostratigraphic and palaeogeographic data considering the context of angiosperm radiation as well as the biota inferred in the amber-bearing outcrops of San Just, Arroyo de la Pascueta and La Hoya (within Cortes de Arenoso succesion). Importantly, the studied assemblages include Afropollis, Dichastopollenites, Cretacaeiporites together with pollen produced by Ephedraceae (known for its tolerance to arid conditions). The presence of these pollen grains, typical for northern Gondwana, associates the Iberian ecosystems with those characterising the mentioned region.
Keywords: Biodiversity; Ecosystem; Amber; ekosystém; pyl; společenstvo; jantar; Pollen; biodiverzita; Biota